THE ROLE OF REFRACTORY FILLER IN THE PROCESSES OF STRUCTURAL FORMATION OF CORE MIXTURES - I. B. Odarchenko; I. N. Prusenko (Литьë и металлургия)
The results of research, computer simulation of the influence of the shape of the grain of sand on the formation of the strength of the core mixture are presented. An essential dependence of the strength of the core on the quality characteristics of the refractory filler is established.